PELATIHAN PENULISAN RENCANA PROGRAM PEMBELAJARAN (RPP) MATA PELAJARAN BAHASA INDONESIA SMP N 1 KUBUNG KABUPATEN SOLOK - Marta, Redo Andi; Rahayu, Zona Rida; Halid, Elan; Putri, Mega; Wirasty. B, Rini (ASOSIASI IDEBAHASA KEPRI, 2024)
The design carried out by teachers can be done creatively and innovatively, or ideas existing in the teachers' minds can be expressed through a lesson plan. However, it must be guided by other instructional elements, such as curriculum, syllabus, and textbooks. Lesson plans vary in different subjects. Specifically, this activity will involve a service project in the form of a training on lesson plans for the Indonesian language subject. Various issues faced by respondents include teachers' uncertainty regarding the components of a lesson plan and their uncertainty about the connection between content and the appropriate teaching media or methods to be applied to that content. The implementation of the service project is carried out by providing socialization to Indonesian language teachers in grades VII, VIII, and IX at Kubung State Junior High School, using methods such as lectures, Q&A sessions, and lesson plan writing exercises. The socialization involves explaining and providing information about the role of teachers in the learning process, the instructional materials prepared by teachers, explaining the components of a lesson plan, elaborating on the Core Competencies and Basic Competencies in the Indonesian language subject, and conducting training for teachers by selecting one of the Basic Competencies in the Indonesian language subject to be designed or developed into a lesson plan. In this context, there are seven lecturers who act as speakers to present the material clearly to Indonesian language teachers.